Biological stability of varieties of black currant against Cecidophyopsis ribis Westw. of the Polish Ukraine - A. Bakalova; H. Tkalenko; O. Derecha; O. Borzykh; N. Hrytsiuk; V. Podziubanchuk (Карантин і захист рослин)
Goal. Study of the biological stability of different varieties of black currant against currant bud mite and determination of its number.